Antiquity of “Sail-Backed” Neural Spine Hyper-Elongation in Mammal Forerunners - Mann, Arjan; Reisz, Robert R. (Frontiers in Earth Science, 2020)
Neural spine hyper-elongation in tetrapods is a unique morphological adaptation that creates a dorsal sail. While this extreme morphology has appeared several times in the evolutionary history of tetrapods, it was first experimented with by the non-mammalian synapsid group known as ‘Pelycosaurs’, famously represented by the Permian apex predator Dimetrodon. Here we provide new fossil data tracing back the evolution of this morphological innovation back to the initial Carboniferous radiation of the synapsid clade. We describe a new hyper-elongated neural spine belonging to the earliest ophiacodontid synapsid Echinerpeton intermedium, from the Pennsylvanian-aged deposits of Florence, Nova Scotia. The new fossil unveils the rapid convergence and repeated evolution of the ‘dorsal sail’ morphology in Synapsida. The development of this trait may have given early synapsids a unique advantage in their early radiation over the other early amniotes, the reptiles.